Thermal decomposition of some diuretic agents - Valladao, D. M S [UNESP]; De Oliveira, L. C S [UNESP]; Zuanon Netto, J. [UNESP]; Ionashiro, Massao [UNESP] (Springer Nature, 1996)
Thermogravimetry-derivative thermogravimetry and differential scanning calorimetry were used to study the thermal behaviour of furosemide, hydrochlorothiazide, spironolactone, and amiloride hydrochloride. The results revealed the extents of their thermal stability and also permitted interpretations concerning their thermal decompositions. © 1996 Akadémiai Kiadó.
Keywords: Diuretic agents; Thermal decomposition; Agents; Differential scanning calorimetry; Drug products; Pyrolysis; Thermodynamic properties; Thermodynamic stability; Amiloride hydrochloride; Furosemide; Hydrochlorothiazide; Spironolactone; Thermoanalysis